ARDS Molecular Phenotypes Have Distinct Lower Respiratory Tract Transcriptomes - Sarma, Aartik; Christenson, Stephanie A; Zha, Beth Shoshana; Pisco, Angela Oliveira; Neyton, Lucile P A; Mick, Eran; Sinha, Pratik S; Wilson, Jennifer G; Moazed, Farzad; Leligdowicz, Aleksandra; Maddali, Manoj V; Siegel, Emily R; et al. (American journal of respiratory and critical care medicine, 2025)
Two molecular phenotypes of the acute respiratory distress syndrome (ARDS) with divergent clinical trajectories and responses to therapy have been identified. Classification as "hyperinflammatory" or "hypoinflammatory" depends on plasma biomarker profiling. Limited data are available about the differences in the pulmonary biology of the molecular phenotypes.RATIONALETwo molecular phenotypes of the acute respiratory distress syndrome (ARDS) with divergent clinical trajectories and responses to therapy have been identified. Classification as "hyperinflammatory" or "hypoinflammatory" depends on plasma biomarker profiling. Limited data are available about the differences in the pulmonary biology of the molecular phenotypes.To identify differences in the pulmonary biology of ARDS molecular phenotypes.OBJECTIVESTo identify differences in the pulmonary biology of ARDS molecular phenotypes.We compared tracheal aspirate gene expression between hyperinflammatory and hypoinflammatory phenotypes in bulk RNASeq from COVID and non-COVID ARDS, and single cell RNASeq from non-COVID ARDS. In a subset of subjects, we also compared plasma proteomic data.MEASUREMENTSWe compared tracheal aspirate gene expression between hyperinflammatory and hypoinflammatory phenotypes in bulk RNASeq from COVID and non-COVID ARDS, and single cell RNASeq from non-COVID ARDS. In a subset of subjects, we also compared plasma proteomic data.In bulk RNASeq analyses, 1157 genes were differentially expressed (FDR < 0.1) between phenotypes in non-COVID ARDS, and 85 genes were differentially expressed between phenotypes in COVID ARDS. 18 genes were reproducibly differentially expressed between phenotypes in both cohorts, including greater expression of IL32, HSPA8, and PPP3CC in hyperinflammatory ARDS. Gene set enrichment analysis identified greater expression of granulopoiesis, T cell and interferon signaling, and integrated stress response pathways in hyperinflammatory ARDS. Network analysis of scRNASeq in a third group of patients identified greater T cell signaling to other immune cells in hyperinflammatory ARDS.MAIN RESULTSIn bulk RNASeq analyses, 1157 genes were differentially expressed (FDR < 0.1) between phenotypes in non-COVID ARDS, and 85 genes were differentially expressed between phenotypes in COVID ARDS. 18 genes were reproducibly differentially expressed between phenotypes in both cohorts, including greater expression of IL32, HSPA8, and PPP3CC in hyperinflammatory ARDS. Gene set enrichment analysis identified greater expression of granulopoiesis, T cell and interferon signaling, and integrated stress response pathways in hyperinflammatory ARDS. Network analysis of scRNASeq in a third group of patients identified greater T cell signaling to other immune cells in hyperinflammatory ARDS.Hyperinflammatory and hypoinflammatory ARDS molecular phenotypes have distinct air space biology. Hyperinflammatory ARDS is characterized by an increased interferon-stimulated gene expression and T cell activation in the lungs. This article is open access and distributed under the terms of the Creative Commons Attribution Non-Commercial No Derivatives License 4.0 (http://creativecommons.org/licenses/by-nc-nd/4.0/).CONCLUSIONSHyperinflammatory and hypoinflammatory ARDS molecular phenotypes have distinct air space biology. Hyperinflammatory ARDS is characterized by an increased interferon-stimulated gene expression and T cell activation in the lungs. This article is open access and distributed under the terms of the Creative Commons Attribution Non-Commercial No Derivatives License 4.0 (http://creativecommons.org/licenses/by-nc-nd/4.0/).